Extended radical resection and chest wall reconstruction for a pulmonary sarcomatoid carcinoma: a case report - Yingzhi Zhao; Shaohua Xie; Haoqian Zheng; Kaixin Zhang; Xin Gao; Wenwu Liu; Wei Dai; Hongfan Yu; Qiuling Shi; Bin Hu; Qiang Li; Tianpeng Xie; et al. (Surgical Case Reports)
Abstract Background Pulmonary sarcomatoid carcinoma (PSC) is a rare and highly malignant type of non-small cell lung cancer (NSCLC), for which the treatment of choice is surgery. For peripheral PSC growing outward and invading the chest wall, a complete resection of the affected lung lobes and the invaded chest wall can improve long-term prognosis. However, when the extent of the resected chest wall is large, reconstruction is often required to reduce the risk of postoperative complications. Here, we present a case of PSC invading the chest wall treated with successful extended radical resection for lung cancer and chest wall reconstruction. Case presentation A 58-year-old male patient with a nodule in the right upper lobe that had been identified on physical examination 2 years before presentation presented to our hospital with a recent cough, expectoration, and chest pain. Imaging revealed a mass in the right upper lobe that had invaded the chest wall. Preoperative puncture pathology revealed poorly differentiated NSCLC. We performed extended radical resection for lung cancer under open surgery and reconstructed the chest wall using stainless steel wire and polypropylene meshes. The procedure was uneventful, and the patient was discharged 7 days postoperatively. Furthermore, the final pathology revealed PSC. Conclusions This case underscores the feasibility of surgical R0 resection in patients with PSC with chest wall invasion and no lymph node metastasis, potentially enhancing long-term outcomes. The novel aspect of this case lies in the individualized chest wall reconstruction for a large defect, using cost-effective materials that offered satisfactory structural support and postoperative recovery, thereby providing a valuable reference for similar future surgical interventions.